2019
DOI: 10.1016/j.ejps.2019.105068
|View full text |Cite
|
Sign up to set email alerts
|

Using mechanistic physiologically-based pharmacokinetic models to assess prenatal drug exposure: Thalidomide versus efavirenz as case studies

Abstract: Maternofoetal physiologically-based pharmacokinetic models integrating multi-compartmental maternal and foetal units were developed using Simbiology® to estimate prenatal drug exposure. Processes governing drug disposition were described using differential equations with key system and drug-specific parameters. Transplacental drug transfer was modelled as bidirectional passive diffusion and benchmarked against those for thalidomide as a control. Model-predictions for pharmacokinetic parameters during pregnancy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 37 publications
1
23
0
Order By: Relevance
“…The present model is an extension of a previously described materno-fetal PBPK model composed of integrated whole-body maternal model and multi-compartmental fetal model ( Supplementary Figure 1 ) ( 28 ). The model was implemented in Simbiology® (v. 9.5, MATLAB® 2018b, Mathworks Inc., Natick, Massachusetts, USA) and extended to include the lymphatic circulation ( Figure 1 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The present model is an extension of a previously described materno-fetal PBPK model composed of integrated whole-body maternal model and multi-compartmental fetal model ( Supplementary Figure 1 ) ( 28 ). The model was implemented in Simbiology® (v. 9.5, MATLAB® 2018b, Mathworks Inc., Natick, Massachusetts, USA) and extended to include the lymphatic circulation ( Figure 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…In some cases where necessary parameter values were not reported, published graph-plots of changes in the parameters: the placental thickness ( 18 ), rates of blood flow through the foramen ovale and ductus arteriosus ( 42 ), over the course of pregnancy were digitized (Plotdigitizer® version 2.6.6, Free Software Foundation, Boston, MA, USA). The data points obtained were used to generate equations of best-fit which were subsequently inputted into the model as previously described ( 28 ). Sensitivity analyses was conducted to observe the extent in which uncertainty in placental diffusion constant propagated into the fetal plasma predictions in the model ( Supplementary Figure 2 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…103 Furthermore, pharmacometric modeling tools such as PBPK modeling could be used to simulate fetal exposures and predict relevant doses for pregnant and lactating women when designing clinical trials. 104,88 Challenges and Opportunities for Future Research Historically, both pregnant women and children have been considered as "therapeutic orphans" because they encompass biologic complexity in Expert Reviews ajog.org terms of dynamic physiology and challenges regarding ethical, legal, logistical, and practical concerns in drug development and drug research. However, the implementation of the Pediatric Research Equity Act (PREA) and Best Pharmaceuticals for Children Act (BPCA) led to a paradigm shift in pediatric therapeutic research.…”
Section: Coronavirus Disease 2019 Treatment and Vaccine Trials In Pregnant And Lactating Womenmentioning
confidence: 99%
“…PBPK models have proved invaluable for predicting the PK of several ARVs [ 69 ], including drug–drug interactions [ 70 , 71 ] and food–drug interactions [ 72 ]. For example, Atoyebi et al applied a similar PBPK model as a case study to predict fetal exposure to EFV and found significantly lower prenatal exposure when compared with known teratogens such as thalidomide [ 73 ]. In silico generation of data on the extent of fetal exposure to drugs may give us more insight into fetal exposure–safety relationships without exposing pregnant women and their fetuses to these teratogenic drugs.…”
Section: Innovative Approachesmentioning
confidence: 99%